Biology Science Literacy of Junior High School Students in South Sulawesi, Indonesia. Issue 1 (February 2021) - Adnan; Mulbar, U; Sugiarti; Bahri, A
Abstract: Science literacy is the ability to use scientific knowledge, identify questions, and draw conclusions based on evidence, in order to understand and make decisions regarding the nature and make the changes to the nature through human activities. This study aims to determine the ability level of biology science literacy of JuniorHighSchool students in South Sulawesi, Indonesia. This research is a survey with the sample of researchchoosed by progressive random sampling with stratification. The sample of this research was third grade of students at junior high school, i.e. SMP 6 Makassar, SMP 26 Makassar, SMPN 4 Sinjai and SMPN 2 Maroswith total students, 220 students. The instrument used to measure the ability of students' biology science literacy was the multiple choice questions consisting of 13 numbers with indicators of scientific literacy, namely: (1) identifying valid scientific opinions; (2) searching for effective literature searches; (3) understanding the elements of research design and how they affect the findings/conclusions; (4) making a precise graph of the data; (5) solving problems using quantitative skills, including basic statistics; (6) understanding and interpreting basic statistics; (7) making inference, prediction and conclusion based on quantitative data. The research data were analyzed descriptively. The results showed that from 220 students, there were no students had a score of biology science literacy in either good or excellent category. The data obtained 25.45% are in the poor category and 74% are in the failure category. It means that teachers need to apply a learning model that can improve students' scientific literacy skills as one of 21st century skills.